AIR DRIED APPLE FORTIFIED WITH VITAMIN E USING MATRIX ENGINEERING - CORTÉS, Misael; OSORIO, Alexander; GARCÍA, Eduard (Vitae, 2009)
The shelf life of air-dried apple products for air at 40°C, fortified with vitamin E has been evaluated in function of colour, texture and stability of vitamin E at different storage conditions. The quantification of vitamin E is carried out using gas chromatography (CG-FID) in the hexane extracts of the samples and the criterion of fortification is 100% IDR/200 g fresh apple. In the end product, don’t found significant influence of the vacuum packaging with the Vitamin E At 4°C and 20°C, the vitamin E was stable, but with high variations in the vitamin E levels, whereas at 30°C, is significant the effect of time. At the 180 days, the vitamin E levels obtained at 4, 20 and 30°C are 82.7, 75.6 and 50% IDR/200 g fresh apple respectively. The vitamin E degradation is modeled by a first order kinetics, and the kinetic constants are fitted by Arrhenius equation. The colour is the parameter determinant in the shelf life, products stored at 4ºC showed acceptable colour characteristics until 180 storage days, while at 20 and 30ºC a darkening of the products is observed from 30 days. The change of texture isn’t relevant in the shelf life.